Development minister characteristics and aid giving - Fuchs, Andreas; Richert, Katharina (European journal of political economy, 2018)
Over 300 government members have had the main responsibility for international development cooperation in 23 member countries of the OECD's Development Assistance Committee since the organization started reporting detailed Official Development Assistance (ODA) data in 1967. Understanding their role in foreign aid giving is crucial since their decisions can influence aid effectiveness and thus economic development on the ground. Our study examines whether development ministers’ personal characteristics are associated with aid budgets and aid quality. To this end, we create a novel database on development ministers’ gender, political ideology, prior professional experience in development cooperation, education, and time in office over the 1967-2012 period. Results from fixed-effects panel regressions show that some of the personal characteristics of development ministers matter. Most notably, we find that more experienced ministers with respect to their time in the development office obtain larger aid budgets. Moreover, our results suggest that female ministers as well as officeholders with prior professional experience in development cooperation and a longer time in office provide higher-quality ODA.
Available online 03 September 2017
Gesehen am 16.12.2019
Impact-Factor: 1.446 (Stand 2019)
SJR Faktor ist 1.107 / Q1 Journal (Stand 2019)
H-Index: 76 (Stand 2019)